Abstract 160: Recurrent Multi‐territorial Ischemic Stroke as an Initial Presentation of Thrombotic Thrombocytopenic Purpura - Grace Marie Nicole Biso; Noah Reichman; Aravind Reddy; Hesham Masoud (Stroke: Vascular and Interventional Neurology)
Introduction Thrombotic thrombocytopenic purpura (TTP) is a rare hypercoagulable disorder characterized by acute hemolytic anemia, thrombocytopenia, neurologic deficits, and renal failure. Here, we describe a young patient with recurrent multi‐territory stroke, with the development of thrombocytopenia later in her course. Her prior diagnosis of etiologies for her ischemic stroke was confounded by the presence of grade 3 PFO and intrinsic arteriopathy attributed to accelerated atherosclerosis due to smoking tobacco with marijuana. Methods A 42‐year‐old woman, active tobacco and marijuana smoker, and recent cryptogenic ischemic and hemorrhagic stroke involving multiple vascular territories with hypercoagulable workup pending, presented with sudden left hemiplegia. Vessel imaging demonstrated irregularity and mild narrowing of the right posterior M2/M3 MCA branches without evidence of large vessel occlusion. MRI showed evidence of evolving left frontal encephalomalacia, prior ischemic stroke on the right inferior MCA and corpus callosum, and prior hemorrhagic stroke on the right parietal and left PCA. In addition, it showed T2 hyperintensities in bilateral anterior and posterior watershed areas. Work‐up was significant for grade 3 PFO/intrapulmonary shunt. Doppler ultrasound was negative for DVT. Basic labs showed LDL 56, A1c 4.8, and TSH 1.8. Hypercoagulable work‐up returned negative. Her platelet count during the admission was initially 169, and 208 on discharge to rehab on single agent antiplatelet (81mg aspirin) and high‐dose statin. After 11 days in rehab, she returned with sudden‐onset slurred speech and right‐sided hemiplegia. Vessel imaging was again negative for LVO and showed significant multi‐vessel arteriopathy. A repeat brain MRI showed a new stroke on the left precentral gyrus, left high frontal lobe, left medial parietal lobe, and left cerebellar hemisphere. The suspected mechanism of stroke was cardioembolic although the patient’s normal left atrial size was presumed to make this mechanism less likely. A few days into admission, her platelets began to decrease. With new‐onset thrombocytopenia (lowest platelet count was 38), ADAMTS screen was ordered and returned positive. The ADAMTS inhibitor Bethesda titer was notably high, 1.4 (nl <0.4). Uncharacteristically for TTP, the patient did not have a fever, anemia (Hb 12), or renal failure (good urine output and Cr 0.7). Nonetheless, given the absence of a clear alternative attributable stroke mechanism, thrombotic thrombocytopenia was suspected as the etiology of her ischemic strokes. For acute therapy, 3‐day 1 mg/kg methylprednisolone was started and hematology service was consulted for co‐management. The patient completed four rounds of plasmapheresis while receiving 90 mg of prednisone daily. She was then started on a regimen to complete four doses of weekly rituximab. The patient improved clinically during the course of her stay and with noted improvements in platelet count and ADAMTS as well. Results N/A Conclusion A low threshold to consider atypical presentations of cryptogenic stroke such as TTP in this case should be in mind when evaluating young adults with recurrent multi‐territory ischemic stroke. Thrombocytopenia may not be present until later in the disease course representing atypical presentations of TTP. As in our case, patients may present without fever, hemolytic anemia, and renal failure.